RELASI HUKUM PIDANA MATERIL DAN HUKUM PIDANA FORMIL DALAM SISTEM PERADILAN PIDANA INDONESIA PASCA KUHP NASIONAL - Basri, Basri; Kurniaty, Yulia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The reform of criminal law through the enactment of the National Criminal Code marks a fundamental shift in Indonesia’s criminal justice system. This reform not only affects the substance of criminal offenses and punishment (substantive criminal law) but also necessitates adjustments in law enforcement mechanisms through procedural criminal law. This article aims to analyze the relationship between substantive criminal law and procedural criminal law within the Indonesian criminal justice system following the enactment of the National Criminal Code, with particular emphasis on normative coherence, systemic function, and its implications for the principles of justice and legal certainty. This study employs a normative juridical method using statutory, conceptual, and systemic approaches, supported by doctrinal analysis and developments in modern criminal law theory. The analysis demonstrates that substantive criminal law and procedural criminal law constitute two inseparable components, as the effectiveness of criminal norms largely depends on the procedures governing their enforcement. However, the findings also indicate the existence of potential disharmony between the reformed substantive criminal law under the National Criminal Code and the procedural criminal law framework, which in part still relies on the structure of the old Criminal Procedure Code. This condition poses risks to legal uncertainty and violations of the principle of due process of law. Therefore, this article emphasizes the importance of integration and synchronization between substantive and procedural criminal law to ensure a criminal justice system that is just, effective, and oriented toward the protection of human rights within the framework of Indonesia as a state governed by the rule of law